The Effect of Information Content and Length on Name Recollection - Etgar, Asaf; Friedman, Ram; Haiman, Shaked; Perez, Dana; Feitelson, Dror G. (2022 IEEE/ACM 30th International Conference on Program Comprehension (ICPC), 2022)
Memorable function and variable names are useful for developers: they reduce the need to re-check how objects are named when one wants to use them, and they enhance comprehension when encountered when reading code. We look at the possible interplay between the information contained in names and how memorable they are. We show in two independent experiments involving a total of 190 subjects that informative names are usually easier to recollect than similar-length names which contain less focused information. Interestingly, we find that less-experienced and female participants are better at remembering the less informative names. We also find that short names, which are not just abbreviated but actually contain less information, are significantly more memorable. Hence a good choice would be to use the the shortest name that includes the most focused and pertinent information.